The Role of Employee Engagement and Gender in the Relationship between Human Resource Management Practices and Employee Job Performance - Thaweepaiboonwong, Jutamard; Thinnam, Thanit (วารสารวิทยาการจัดการ มหาวิทยาลัยเกษตรศาสตร์, 2025)
This study investigates how human resource management (HRM) practices influence employee job performance, with employee engagement acting as a mediator, and explores whether gender moderates this relationship. Survey data were collected from 268 employees at large manufacturing firms in Thailand and analyzed using structural equation modeling. The results indicate that employee engagement partially mediates the relationship between HRM practices and job performance, while gender does not moderate this relationship. These findings enhance our understanding of the interaction between HRM practices and employee engagement and offer practical guidance for developing effective HRM strategies and engagement programs in emerging-market manufacturing contexts.